Odpowiedź:
[tex]b)\\\\a=(2^3\cdot2^4)^5=(2^{3+4})^5=(2^7)^5=2^{35}\ \ \ \ \ \ 1\\\\b=(2^{10}:2^8)^9=(2^{10-8})^9=(2^2)^9=2^{18}\ \ \ \ 3\\\\c=(2^5)^4\cdot2^7=2^{20}\cdot2^7=2^{20+7}=2^{27}\ \ \ \ \ \ 2[/tex]
[tex]d)\\\\a=((\frac{1}{3})^3)^4=(\frac{1}{3})^{12}\ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ 3\\\\b=(\frac{1}{3})^4\cdot\frac{1^5}{3^5}=(\frac{1}{3})^4\cdot(\frac{1}{3})^5=(\frac{1}{3})^{4+5}=(\frac{1}{3})^9\ \ \ \ \ \ 2\\\\c=(\frac{1}{3})^8\cdot(\frac{1}{3})^2:(\frac{1}{3})^3=(\frac{1}{3})^{8+2-3}=(\frac{1}{3})^7\ \ \ \ \ \ \ \ \ \ 1[/tex]